Analisis Kepuasan Pelanggan Terhadap Pelayanan Customer Service Kereta Api Bandara Yogyakarta Internasional Airport - Ardi Surwiyanta; Siti Warsih (Journal of Tourism and Economic, 2024)
This research aims to determine the level of customer satisfaction with customer service on the Yogyakarta International Airport Railway. In this research, the data collection method uses four data collection techniques, namely questionnaires, interviews, literature studies, analysis documentation using quantitative descriptive methods. Meanwhile, data analysis was carried out using qualitative descriptive analysis. Customer satisfaction with customer service in the tangible dimension: 35% said they were very satisfied and 53% said they were satisfied. In the responsiveness dimension, 25% said they were very satisfied and 62% said they were satisfied. In the Assurance dimension, 34% said they were very satisfied and 58% said they were satisfied and in the Empathy dimension, 46% said they were very satisfied and 32% said they were satisfied. Meanwhile, 8% were less satisfied and 6% were dissatisfied. Overall, from the 4 dimensions (tangible, responsiveness, assurance, and empathy) 35% of respondents said they were very satisfied with customer service and 49% said they were satisfied. The remaining 16% said they were dissatisfied and dissatisfied.